Gingival crevicular fluid as biomarker's source for Alzheimer's disease = Fluido crevicular gingival como biomarcador de enfermedadde Alzheimer - Sansores España, Luis Daniel; Morales, Francisca; Arriola Pacheco, Fabio; Astorga, Jessica; Paula Lima, Andrea (2022)
Periodontitis is a low-grade inflammatory disease caused by a subgingival dysbiotic microbiota. Multiple studies have determined the higher prevalence of tooth loss and poor oral hygiene in patients with Alzheimer's disease (AD). However, the periodontal diagnosis, periodontal bacteria or mediators has not been measured to date. Aim: To determine the periodontal status, the pro-inflammatory mediators, Porphyromonas gingivalis load, and Apoliporpotein E (ApoE) in patients with AD. A complete dental examination was performed on 30 patients, and cognitive status was determined by the Montreal Cognitive Assessment (MoCA). Subgingival microbiota and GCF samples were then taken from all patients from the deepest sites. Total DNA was isolated from the microbiota samples for the quantification of the 16S ribosomal subunit. Pro-inflammatory mediators and ApoE were quantified from the gingival crevicular fluid (GCF). Patients with AD had periodontitis stage III-IV in 80%, a higher concentration of pro-inflammatory and ApoE mediators, and a higher P. gingivalis load compared to healthy subjects. The pro-inflammatory mediators, P. gingivalis load had a negative correlation with the MoCA test scores. Finally, a ROC curve was performed to assess the specificity and sensitivity of ApoE levels, detecting an area of 84.9%. In AD patients, we found a more severe periodontitis, a higher levels of pro-inflammatory mediators, and higher bacterial load. In addition, there is an increase in ApoE that allows to clearly determine patients with health, periodontitis and periodontitis and AD.
La periodontitis es una enfermedad crónica no transmisible que se caracteriza por generar una inflamación sistémica de bajo grado causada por una microbiota disbiótica subgingival. Múltiples estudios han determinado la mayor prevalencia de pérdida de dientes y mala higiene bucal en pacientes con enfermedad de Alzheimer (EA). Sin embargo, el diagnóstico periodontal, bacterias periodontales o mediadores pro-inflamatorio no se ha medido hasta la fecha. Determinar el estado periodontal, los mediadores pro-inflamatorios, la carga de Porphyromonas gingivalis y la apoliporpoteína E (ApoE) en pacientes con EA. Se realizó un examen odontológico completo en 30 pacientes y el estado cognitivo se determinó mediante la Evaluación Cognitiva de Montreal (MoCA). Luego, se tomaron muestras de microbiota subgingival y FCG de todos los pacientes de los sitios más profundos. Se aisló el DNA total de las muestras de microbiota para la cuantificación de la subunidad ribosómica 16S. Los mediadores pro-inflamatorios y la ApoE se cuantificaron a partir del líquido crevicular gingival (GCF). Los pacientes con EA tenían periodontitis en estadio III-IV en 80%, una mayor concentración de mediadores pro-inflamatorios y ApoE, y una mayor carga de P. gingivalis en comparación con los sujetos sanos. Los mediadores pro-inflamatorios y la carga de P. gingivalis tuvieron una correlación negativa con las puntuaciones de la prueba MoCA. Finalmente, se realizó una curva ROC para evaluar la especificidad y sensibilidad de los niveles de ApoE, detectando un área del 84,9%. En los pacientes con EA encontramos una periodontitis más severa, mayores niveles de mediadores pro-inflamatorios y mayor carga bacteriana. Además, un aumento de ApoE que permite determinar claramente a los pacientes con salud, periodontitis y periodontitis y EA.
En revista Odóvtos, vol. 24, no.1 (enero-abril 2022)
Descripción basada en el contenido visto el 15 de noviembre, 2024
También disponible en formato HTML y EPUB